Analysis of Static and Cyclic Properties of 316L and AlSi10Mg in Conventional Casting and Additive Manufacturing - Chmelko, Vladimír; Margetin, Matúš; Zetková, Ivana; Norek, Martin; Likavčan, Filip (Materials (Basel, Switzerland), 2024)
The paper presents the original results of cyclic testing of materials that are identical in chemical composition but produced by two different technologies: conventional metallurgy and additive manufacturing. For the aluminium alloy AlSi10Mg and the austenitic steel 316L, tensile curves, tension-compression and torsion alternating fatigue curves are experimentally obtained and presented. The experimental results are compared for two fabrication technologies-conventional metallurgy and additive DLMS technology. The results indicate a significant effect of anisotropy on the fatigue performance of the AM materials and a different slope of the fatigue life curves in the cyclic torsion versus cyclic tension-compression. The static and, in particular, the fatigue properties of both materials are discussed in relation to the microstructure of the materials after conventional production and after additive manufacturing. This comparison allowed us to explain both the causes of the anisotropy of the AM materials and the different slope of the curves for normal and shear stresses under cyclic loading. Using the example of the strength assessment of bicycle frames, the possibility of progressively wider use of additive manufacturing for load-bearing structures is presented.
Keywords: 316L; aluminium alloy; fatigue properties; tension and torsion cyclic tests; additive manufacturing